2012
DOI: 10.1007/s00595-012-0461-9
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment for an asymptomatic and unruptured sinus of Valsalva aneurysm: report of a case

Abstract: A 70-year-old male underwent a transthoracic echocardiography as a screening test for hypertension and an unruptured aneurysm was detected in the right sinus of Valsalva. The right sinus of Valsalva aneurysm obstructed the right ventricle outflow tract but he did not have any symptoms. The sinus of Valsalva aneurysm was treated successfully by a patch closure with a bovine pericardial patch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Additionally, the standard remodeling technique was difficult to perform without an aortic remnant. Conversely, a study on patch closure reported that a single SVA was successfully repaired using sutures with pledgets, which were inserted into the aortic valve annulus from the left ventricular side to the aortic side [10]. Although this technique could possibly be applicable in the current patient, he had two SVAs on both sides of the commissure between the left and right coronary cusps, and preserving the aortic valve geometry after double patch closure was difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the standard remodeling technique was difficult to perform without an aortic remnant. Conversely, a study on patch closure reported that a single SVA was successfully repaired using sutures with pledgets, which were inserted into the aortic valve annulus from the left ventricular side to the aortic side [10]. Although this technique could possibly be applicable in the current patient, he had two SVAs on both sides of the commissure between the left and right coronary cusps, and preserving the aortic valve geometry after double patch closure was difficult.…”
Section: Discussionmentioning
confidence: 99%